Inspirational Intuition – Bridge to Future Viability - Jochem Müller (ZBW - Leibniz Information Centre for Economics, 2023)
The management of companies should recognize the important role of the intuitive competence of employees and make it available for knowledge generation. There is a special role and relevance of Inspirational Knowledge Imagination, for creating inventions and innovations, as a source of competitive advantage and future viability. A newly developed inventory for self-estimation of intuitive competence helps to unlock these competitive advantages. Based on a selective analysis of relevant literature research and studies, a ten-question questionnaire was created using a Likert scale for the self-estimating Inspirational Knowledge Imagination Inventory (IKII-10). The originally designed questionnaire was tested and extractable principal components were found, using Principal Component Analysis. This is done to describe Inspirational Intuition in more detail so that it could be further approached in terms of content. Possible applications of the intuitive, inspirational competence in the innovative business context, will give the management suggestions for professional use of the intuitive abilities and their targeted development. Intuitive competence, in the sense of an inspirational knowledge imagination, can promote the development of new knowledge and build an intuitive bridge to an imaginary and divined world. – – Das Management von Unternehmen sollte die wichtige Rolle der intuitiven Kompetenz von Mitarbeitern erkennen und sie für die Wissensgenerierung verfügbar machen. Eine besondere Rolle und Relevanz kommt dem Inspirationswissen Imagination zu, um Erfindungen und Innovationen zu schaffen, als Quelle für Wettbewerbsvorteile und Zukunftsfähigkeit. Ein neu entwickeltes Inventar zur Selbsteinschätzung der intuitiven Kompetenz hilft, diese Wettbewerbsvorteile zu erschließen. Auf der Grundlage einer selektiven Analyse einschlägiger Literaturrecherchen und Studien wurde ein zehn Fragen umfassender Fragebogen mit einer Likert-Skala für das Inventar zur Selbsteinschätzung von Inspirational Knowledge Imagination (IKII-10) entwickelt. Der ursprünglich entworfene Fragebogen wurde getestet und es wurden extrahierbare Hauptkomponenten mit Hilfe der Hauptkomponentenanalyse gefunden. Dies geschieht, um die Inspirationale Intuition genauer zu beschreiben, damit sie inhaltlich weiter erschlossen werden kann. Mögliche Anwendungen der intuitiven, inspirierenden Kompetenz im innovativen Unternehmenskontext sollen dem Management Anregungen für den professionellen Einsatz der intuitiven Fähigkeiten und deren gezielte Entwicklung geben. Intuitive Kompetenz im Sinne einer inspirierenden Wissensvorstellung kann die Entwicklung von neuem Wissen fördern und eine intuitive Brücke zu einer imaginären und geahnten Welt schlagen.
Keywords: A1; M1; 330; Intuition; Innovation; Inspiration; Knowledge; Imagination; Inventory; Creativity; Competence; Principal Component Analysis; Questionnaire; Leadership; Future Viability